SCREENING OF ALKALIPHILIC, HALOALKALIPHILIC BACTERIA AND ALKALITHERMOPHILIC ACTINOMYCETES ISOLATED FROM ALKALINE SODA LAKE OF LONAR, INDIA FOR ANTIMICROBIAL ACTIVITY - SUCHITRA B. BORGAVE; AMARAJA A. JOSHI; ANITA S. KELKAR; PRADNYA P. KANEKAR (International Journal of Pharma and Bio Sciences, 2012)
Twelve moderately haloalkaliphilic bacteria were isolated from sediment and water sample collected from the alkaline Soda Lake of Lonar, India using Lonar Lake water as enrichment medium. All the isolates were identified based on biochemical characterization, 16S rRNA sequencing and phylogenetic analysis. Isolation of haloalkaliphilic Marinobacter excellens, Alkalimonas delamerensis, Roseinatronobacter monicus and Rhodobaca bogoriensis from Lonar Lake appears to be the first report. Three alkalithermophilic actinomycetes isolated from sediment sample of Lonar Lake using glucose yeast-extract peptone medium were identified as Laceyella sacchari belonging to family Thermoactinomycetaceae. All the 12 bacterial isolates along with 66 previously isolated and identified isolates from Lonar Lake (total 78 isolates) and three isolates of alkalithermophilic actinomycetes were screened for their antimicrobial activity. The alkaliphilic bacteria isolated from Lonar Lake exhibited inhibitory effect against clinical isolates of pathogenic bacteria and phytopathogenic fungi which indicates the possibility of using alkaliphilic bacteria as biological control agents.